2014
DOI: 10.1080/00207233.2014.881165
|View full text |Cite
|
Sign up to set email alerts
|

Public consent for the geologic disposal of highly radioactive wastes and spent nuclear fuel

Abstract: Global agreement exists for the policy of the geological disposal of spent nuclear fuel and high-level radioactive wastes, provided that there is public consent. To gain consent, social scientists recommend the less competitive approach of consensus rather than the majority rule (MR) of democracies. But, we hypothesize, competition for public consent from MR best improves the quality and stability of choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 21 publications
1
32
0
Order By: Relevance
“…We also found that economic freedom and corruption were inversely correlated significantly (r = −0.77, p < 0.025), indicating that an increase in freedom was associated with a decrease in corruption. Heartened by these pilot results, we were ready to test our hypothesis with Equation (15). For Q 1 , we summed the result of FMD versus MPD to get 1.78.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We also found that economic freedom and corruption were inversely correlated significantly (r = −0.77, p < 0.025), indicating that an increase in freedom was associated with a decrease in corruption. Heartened by these pilot results, we were ready to test our hypothesis with Equation (15). For Q 1 , we summed the result of FMD versus MPD to get 1.78.…”
Section: Resultsmentioning
confidence: 99%
“…Information constraints (barriers) under authoritarian regimes are less able to direct the movement of labor and capital to best solve targeted problems, an added constraint for innovation, one reason the Chinese rely on the theft of intellectual property (see the interview of General M. Hayden, the former CIA and NSA chief, by the editor-in-chief of the Wall Street Journal, [66]). Certainly, obstacles exist in democracies, especially when they become less free to allocate resources to solve the problems targeted (e.g., the Department of Energy's practices included cardboard boxes, seepage basins and other shortcuts to dispose of its radioactive wastes to save money that may eventually cost DOE well over two hundred billions of dollars to remediate its Hanford Site and its Savannah River Site; in Lawless [15]). Unlike Google's survey of teams [32], guided as it was by traditional social science, we have conjectured and found evidence that an improved theory of human behavior includes both cognitive (subjective surveys like Google's) and behavioral (physical) data which our quantum-like model handles well.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations